Assessment of the Preferred Methods Used by Mothers to Prevent Malaria Infection among Children Under Five Years in the Hohoe Municipality Of Ghana - Adjuik, Martin; Takramah, Wisdom; Kudzo Axame, Wisdom; Owusu, Richard; Atta Parbey, Phyllis; Tarkang, Elvis (Journal of Preventive Medicine And Care, 2017)
Background: The use of Long Lasting Insecticide Nets (LLINs) is seen as a major public health intervention and has shown to have both direct and indirect effects on the dynamics of malaria transmission. This report assessed the methods used by mothers to prevent malaria infection among their children under five years in the Hohoe Municipality. Method: A cross-sectional survey carried out in February 2017 among 418 mothers with children under five. Data were collected in the form of interviews using questionnaires on the usage of LLIN alone, LLIN with other methods (LLIN+) and use of other methods only (OMs). Chi square test and multinomial logistic regression were used to determine the association between dependent and independent variables. Results: Of the 418 mothers, 28.5% used LLIN only, 50.7% used LLIN+ and 20.8% used OMs only to prevent malaria. Mothers aged 30-39 and 40-49 years were 3.87 and 5.55 times more likely to use LLIN only rather than OMs as compared to those aged less than 20 years (AOR=3.87, p=0.019) and (AOR=5.55, p=0.029) respectively. Similarly, mothers aged 30-39 and 40-49 years were 3.08 and 4.02 times more likely to use LLIN+ rather than OMs as compared to those aged less than 20 years (AOR=3.08, p=0.023) and (AOR=4.02, p=0.050) respectively. Mothers who attained a higher level of education were 2.08 times more likely to use LLIN+ rather than OMs as compared to those with no formal education (AOR=2.08, p=0.015). Those who resided in rural areas were 2.00 times more likely to use LLIN only and LLIN+ rather than OMs only as compared to urban dwellers (AOR=2.00, p=0.002) and (AOR=2.00, p=0.013) respectively. Conclusion: More than half of the mothers preferred using LLIN+. One out of 3 mothers used only LLIN while one out of 5 used OMs only to prevent malaria. Age, educational level and place of residence were significantly associated with methods used to prevent malaria. There is the need for targeted education on LLINs in order to improve usage among younger mothers and mothers residing in urban areas. Further investigations to determine reasons for using OMs only and also determine the added value of OMs to LLINs in preventing malaria are recommended.
Keywords: Mothers; Malaria Prevention; Preferred Method; LLIN; Other Methods; Hohoe Municipality; Ghana